Using Adaptive Management to Meet Conservation Goals - Franklin, Thomas M; Helinski, Ronald; Manale, Andrew (Fish and Wildlife Response to Farm Bill Conservation Practices, 2007)
Natural resource professionals should know whether or not they are doi ng an effective job of managing natural resources. Their decision-maki ng process should produce the kind of results desired by the public, e lected officials, and their agencies’ leadership. With billions of dol lars spent each year on managing natural resources, accountability is more important than ever. Producing results is the key to success. Man agers must have the necessary data to make enlightened decisions durin g program implementation—not just at the conclusion of a program. Adap tive management is described as an adapt-and-learn methodology as it p ertains to implementing Farm Bill conservation practices. Four regiona l case studies describe how adaptive management is being applied by pr acticing fish and wildlife managers. Indicators were identified to mon itor and evaluate contributions to fish and wildlife habitat for each of the case studies. Data collected at each stage of the studies were used to make mid-course adjustments that enabled leadership to improve or enhance ongoing management actions.